2014
DOI: 10.1016/j.jvs.2013.06.072
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus open saphenous vein graft harvest for lower extremity bypass in critical limb ischemia

Abstract: Objectives Endoscopic vein harvest (EVH) has been demonstrated to improve early morbidity when compared with conventional open harvest technique (OVH) for infrainguinal bypass surgery. However recent literature suggests conflicting results regarding mid and long-term patency with EVH. The purpose of this study is to compare graft patency between harvest techniques specifically in patients with critical limb ischemia (CLI). Methods This retrospective study compared two groups of patients (EVH=39 and OVH=49) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
6
24
0
Order By: Relevance
“…This was also reflected in the multivariate analysis, which identified OVH as an independent risk factor for wound complications. Our findings are similar to the report of Eid et al, 10 who showed that 20% of the open harvest group had vein harvest site complications, whereas there were none in the endoscopic group (14.5% vs 0% in our study). Similarly, Santo et al 11 also showed a significant difference in the vein harvest site complication rates (29.1% vs 11.8%) between the two techniques, although the overall wound complication rates were similar (44.4% vs 36.7%).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This was also reflected in the multivariate analysis, which identified OVH as an independent risk factor for wound complications. Our findings are similar to the report of Eid et al, 10 who showed that 20% of the open harvest group had vein harvest site complications, whereas there were none in the endoscopic group (14.5% vs 0% in our study). Similarly, Santo et al 11 also showed a significant difference in the vein harvest site complication rates (29.1% vs 11.8%) between the two techniques, although the overall wound complication rates were similar (44.4% vs 36.7%).…”
Section: Discussionsupporting
confidence: 92%
“…Although our overall wound complication rate of 43% in the OVH group seems high, it includes all complications including Szilagyi I, and it is not too dissimilar from the previous reported rates in series from single academic centers (23%-44%). 10,11,15,19 Our study also found that both BMI and prior surgery were independently associated with wound complications. The relationship between increased BMI and surgical wound complications has been demonstrated in several previous studies.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations